2009
DOI: 10.1021/ef9000924
|View full text |Cite
|
Sign up to set email alerts
|

Lab-scale Investigation of Deposit-induced Chlorine Corrosion of Superheater Materials under Simulated Biomass-firing Conditions. Part 1: Exposure at 560 °C

Abstract: Deposit-induced chlorine corrosion was studied under well-controlled laboratory conditions, simulating the conditions in straw-fired boilers and boilers cofiring coal and straw. This was done by exposing pieces of superheater tube (TP 347H FG) covered with synthetic deposits of known Cl content to gas mixtures simulating straw-firing and cofiring of coal and straw, at 560°C (1040°F), for 3 days. The corroded specimens, and the reacted deposits, were studied in detail using a scanning electron microscope to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…In order to preserve the integrity of the chlorides and other water-soluble compounds on the samples, post-test polishing was done without a lubricant 11,12 . The samples were then examined using an Olympus BX51M optical microscope and a Hitachi S-4700 scanning electron microscope (SEM), to measure the depth of corrosion and provide insight into the subsurface material degradation and structure of the corrosion layer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to preserve the integrity of the chlorides and other water-soluble compounds on the samples, post-test polishing was done without a lubricant 11,12 . The samples were then examined using an Olympus BX51M optical microscope and a Hitachi S-4700 scanning electron microscope (SEM), to measure the depth of corrosion and provide insight into the subsurface material degradation and structure of the corrosion layer.…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that the corrosion process can be severe in air but can also be increased modestly by the presence of SO 2 which can cause intra-deposit sulfation of alkali chlorides releasing HCl or Cl 2 close to the metal surface 6,10,11 . Lith et al 12 showed that the degree of sulfation of KCl in the deposit in the presence of SO 2 does not necessarily influence corrosion rate. An increase in SO 2 has also been shown to decrease corrosion rate through conversion of KCl in the flue gas to the less corrosive K 2 SO 4 13,14 .…”
Section: R6mentioning
confidence: 99%
See 1 more Smart Citation
“…e content of HCl and SO 2 is adjusted through a flow meter. ey are mixed well in the gas mixing device in order to simulate the flue gas atmosphere in the boiler superheater [13]. e high-temperature reaction part adopts a horizontal tube furnace electric heating system.…”
Section: Experimental Systemmentioning
confidence: 99%
“…e component of deposits varies widely as the fuel characteristics, combustion conditions, and other factors. Lith et al [13] suggest that the corrosion in the process of cofiring of biomass and coal is mainly based on the alkali metals existed in deposits.…”
Section: Effect Of Fuel Property On Deposit Corrosionmentioning
confidence: 99%